AIHA laboratory quality assurance manual - Teague, Andrew L.; Eide, Mary E. (American Industrial Hygiene Association, 2019)
This manual describes the major elements of a reliable industrial hygiene laboratory quality system. The manual was compiled to aid new laboratories in establishing quality programs and to help established laboratories enhance existing programs. It is not intended as a "turn-key" document, but rather as a reference manual, the parts of which can be adapted to the individual laboratory. The updated manual addresses requirements of ISO/IEC 17025:2017 as well as new AIHA® LAP Policies released in 2018. By incorporating the basic principles outlined in this manual, laboratories can develop comprehensive programs that will assure quality results.